Earning more and getting less : why successful wives can't buy equality - Tichenor, Veronica Jaris, 1963- (Rutgers University Press, 2005)
Annotation Shows how, historically, men derived a great deal of power over financial and household decisions by bringing home all (or most) of a family's income. The author demonstrates how wives, instead of using their substantial incomes to negotiate more egalitarian relationships, enable their husbands to perpetuate male dominance within the family.